Plano Municipal de Educação de Sorocaba/SP: monitoramento, avaliação e controle social - Almenara, Gilsemara Vasques Rodrigues (Universidade Federal de São Carlos, 2024)
The objective of this research in education policy and management areas was to analyze the debates and clashes in the light of the instances responsible for monitoring and evaluating the PME (Municipal Education Plan) of Sorocaba/SP, regarding the monitoring flow, evaluation flow and referrals for correction of the goals set out in the document (PME), based on the dimension of social control, in the period 2015-2020. The PME was a requirement of the National Education Plan - Law No. 13,005, of June 25, 2014 (Brazil, 2014), which specifies, in Article 8, the requirement of elaboration and / or adequacy of the Municipal Education Plans within one year, counted from this law, which approved the National Education Plan (2014 - 2024), and which determined as the responsibility of the states and municipalities to elaborate respectively their plans in a democratic way, in order to ensure the effective participation of society. The research was limited to the period 2015-2020. The methodology was developed through qualitative research, consisting of bibliographic and documentary analysis and interviews based on a semi-structured script of questions. Data treatment was performed through content analysis, based on Bardin (1977). Three actors contributed to the data collection (03), being a component of the Technical Support Team of the PME, a member of the Permanent Education Forum and a member of the Municipal Council of Education. The results show that: the municipality of Sorocaba did not carry out its biennial stages of Monitoring and Evaluation of the PME, which directly affects the quality of public educational policies and the quality of education. Keywords: Municipal Education Plan; Monitoring and Evaluation; Social Control; Sorocaba/SP.

El objetivo de esta investigación en el área de política y gestión de la educación fue analizar los debates y enfrentamientos a la luz de los órganos responsables del seguimiento y evaluación del PME (Plan Municipal de Educación) en la ciudad de Sorocaba/SP, en términos de flujo de seguimiento, flujo de evaluación y remisiones para la corrección de las metas establecidas en el documento (PME), con base en la dimensión de control social, en el período 2015-2020. El PME fue una exigencia del Plan Nacional de Educación - Ley nº 13.005, de 25 de junio de 2014 (Brasil, 2014), que especifica, en su artículo 8º, la exigencia de elaborar y/o adecuar los Planes Municipales de Educación en el plazo de un año a partir de esta ley, que aprobó el Plan Nacional de Educación (2014 - 2024), y que determinó que era responsabilidad de los estados y municipios elaborar sus planes de forma democrática, para garantizar la participación efectiva de la sociedad. La investigación se limitó al período 2015-2020. La metodología se desarrolló a través de una investigación cualitativa, consistente en análisis bibliográfico y documental y entrevistas basadas en un guión semiestructurado de preguntas. Los datos se procesaron mediante análisis de contenido, basado en Bardin (1977). Tres encuestados contribuyeron a la recogida de datos: un miembro del Equipo de Apoyo Técnico del PME, un miembro del Foro Permanente de Educación y un miembro del Consejo Municipal de Educación. Los resultados muestran que: el municipio de Sorocaba no ha realizado sus etapas bienales de Seguimiento y Evaluación del PME, lo que afecta directamente a la calidad de las políticas públicas educativas y a la calidad de la educación. Palabras Clave: Plan Municipal de Educación; Seguimiento y Evaluación; Control Social; Sorocaba/SP.
Sorocaba/SP Municipal Education Plan: monitoring, evaluation and social control
Plan Municipal de Educación de Sorocaba/SP: seguimiento, evaluación y control social
Keywords: Plano Municipal de Educação; Monitoramento e Avaliação; Controle Social; Sorocaba/SP; Municipal Education Plan; Monitoring and Evaluation; Social Control; Plan Municipal de Educación; Monitoreo y Evaluación; Control Social; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::PLANEJAMENTO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL